Bibliometric Analysis of Healthcare Failure Mode and Effect Analysis Research - Ariadne Aulia; Elsye Maria Rosa (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2023)
Healthcare Failure Mode and Effect Analysis (HFMEA) has been widely used as a proactive risk assessment for healthcare processes since its development in 2001. This study performs a bibliometric analysis of published papers on HFMEA to map its utilization and evolutionary nuances. The dataset was obtained from the Scopus database for English-language papers published between 2002 and 2022 using “HFMEA” or “Healthcare Failure Mode and Effect Analysis” in the article title, abstract, or keywords. Microsoft Excel and VOSviewer were used to perform the analysis. The authors found 230 relevant publications during the study period. The year 2020 has the most publications, with 34 papers. Articles written by DeRosier et al. received the most citations (470). The United States had the highest number of published papers (84), while the United Kingdom had the most international collaboration. Co-occurrence analysis of author keywords showed that patient safety, risk assessment, and risk management were high-rank words. This study emphasizes scholarly collaboration trends and identifies relevant authors, topics, and journals on HFMEA research. It may assist health practitioners and healthcare facility managers in understanding the focus of HFMEA research. Nonetheless, the number of HFMEA publications is still sparse. Further studies on HFMEA in underrepresented medical specialties should be explored.